2021
DOI: 10.3390/ani11082195
|View full text |Cite
|
Sign up to set email alerts
|

Isoquinoline Alkaloids in Sows’ Diet Reduce Body Weight Loss during Lactation and Increase IgG in Colostrum

Abstract: Isoquinoline alkaloids (IQ) exert beneficial antimicrobial and anti-inflammatory effects in livestock. Therefore, we hypothesized that supplementing sows’ diets with IQ during gestation would decrease farrowing stress, affecting the piglets’ development and performance. Sows were divided into: IQ1, supplemented with IQ from gestation day 80 (G80) to weaning; IQ2, supplemented from gestation day 110 (G110) to weaning, and a non-supplemented (NC) group. Sow body weight (BW), feed intake, back-fat thickness and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Additionally, IQ-fed finishing pigs have demonstrated lower levels of cortisol after transportation to slaughter, which was positively correlated to a decrease in Salmonella shedding, indicating that IQ supplementation reduces stress in pigs and the negative impact on the gastrointestinal tract [ 2 ]. In sows, it has been recently demonstrated that IQ supplementation during lactation reduced body weight loss and increased colostrum quality [ 1 ]. De Souza Massei et al [ 6 ] have recently investigated the effect of IQ supplementation on performance parameters, carcass characteristics and health in growing and finishing pigs under experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, IQ-fed finishing pigs have demonstrated lower levels of cortisol after transportation to slaughter, which was positively correlated to a decrease in Salmonella shedding, indicating that IQ supplementation reduces stress in pigs and the negative impact on the gastrointestinal tract [ 2 ]. In sows, it has been recently demonstrated that IQ supplementation during lactation reduced body weight loss and increased colostrum quality [ 1 ]. De Souza Massei et al [ 6 ] have recently investigated the effect of IQ supplementation on performance parameters, carcass characteristics and health in growing and finishing pigs under experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…19 This could be attributed to the presence of alkaloids and saponins in the aqueous extract of Rumex usambarensis, which have shown to have some weight reduction activity. 19,[24][25][26] Appetite being the desire to eat food, makes it a qualitative outcome and therefore difficult to quantify in a valid and reliable way. 27 Because appetite is directly proportional to food intake, a measure of food intake can indirectly measure appetite.…”
mentioning
confidence: 99%